Screening Of Soybean Genotypes To Short Period Of Flooding - Pokhrel, Anil; Shrestha, Renuka; Dangi, S.R. (Agronomy Journal of Nepal, 2021)
High soil moisture stress owing to heavy rainfall during the early growth stage is the most limiting factor affecting the growth and productivity of soybean in the Terai region of Nepal. This study was conducted to identify the soybean cultivars suitable for high soil moisture stress condition. Sixteen cultivars of soybean were planted under two soil moisture conditions namely, (a) short term flooded and (b) normal growing conditions in two consecutive years 2018 and 2019. Six stress tolerance indices like stress tolerance (TOL), stress susceptibility index (SSI), yield stability index (YSI), yield index (YI), mean productivity (MP) and geometric mean productivity (GMP) were calculated based on seed yields under flooded and normal conditions. The combined analysis showed that soybean cultivar SBO–115 (1912 kg/ha) and TGX 1990–94F (1883 kg/ha) produced significantly the highest seed yield under normal and flooded conditions, respectively. These two cultivars TGX 1990–94F (YI =1.3) and SBO–115 (YI =1.2) also possess the highest value of yield index. In contrast, the yield stability index was found maximum in cultivar LS –77 –16 –16 with a value of 1.4. Similarly, correlation analysis showed that soybean yield under flooded condition had a significant and positive association with yield under normal condition, YI, MP and GMP, while negative association found with TOL and SSI. This study indicated that the cultivars TGX 1990 – 94F, G –1873 and Kavre found to be more stable in two different conditions, while cultivars TGX 1990–94F and SBO –115 found suitable for flooded condition. These cultivars can be used directly or further in the crossing program for breeding high moisture stress tolerance cultivars.